FRI0047 Elevated 14-3-3eta levels predict worse radiographic outcomes in patients with recent-onset inflammatory arthritis in clinical remission. (15th June 2017) - Carrier, N; Garant, M-P; Marotta, A; Fernandes, AJ De Brum; Liang, P; Masetto, A; Gui, Y; Savill, J; Michienzi, S; Maksymowych, WP; Boire, G
Abstract : Background: 14–3-3η is a joint-derived serum protein that up-regulates pro-inflammatory factors. We have previously reported that baseline 14–3-3η levels ≥0.50 ng/ml (HIGH 14–3-3η) were predictive of radiographic progression over 5 years. Objectives: Our objective was to verify if the persistence of HIGH 14–3-3η at 18 months in recent-onset polyarthritis patients in REMISSION predicts more rapid radiographic progression over the following years, up to 42 months. Methods: Serum 14–3-3η titres were assessed at baseline and at 18 months into disease, a median of 14 months after diagnosis and initiation of treatment. Three definitions of "clinical remission" at 18 months were used: Swollen Joint Count (SJC) =0; SJC + Tender Joint Count (TJC) =0; ACR/EULAR Boolean definition. The progression of radiographic damage (Erosion and Total Sharp/van der Heijde (SvH) scores) in patients with LOW (<0.50 ng/ml) or HIGH (≥0.50 ng/ml) 14–3-3η were compared using the Mann-Whitney test. P values <0.05 were considered significant. Results: Out of 331 patients, 36.0% of which had HIGH 14–3-3η at Baseline, 308 had complete data up to 5 years. Median age was 60 years, 62% women. Depending on the stringency of the definition used, variable numbers of patients reached remission at 18 months: 162 (53%) had SJC=0; 108 (35%) SJC+TJC=0; and 56 (18%) Boolean. Remission at 18 months was negatively associated with persistence of HIGH 14–3-3η since HIGH 14–3-3η were then present in 32/162 (19.7%) SJC=0 patients; 22/108 (20.4%) SJC+TJC=0 and 13/56 (23.2%) Boolean. Compared to patients in remission with LOW 14–3-3η, patients in remission with HIGH 14–3-3η at 18 months had numerically faster subsequent progression with all definitions. For example, in patients with Boolean remission, mean (SD) erosion progression over 42 months was 7.2±13.1 vs 1.5±3.3 and mean (SD) progression of Total score 9.2±14.5 vs 2.8±4.4 units (Figure). However, due to low numbers and limited power, differences in progression were statistically significant only for the less strict definitions of remission and only over the following year: Erosions (SJC=0, p=0.0042, SJC+TJC=0, p=0.0236), Total score (SJC=0, p=0.0146; with a trend for SJC+TJC=0, p=0.077). None of the comparisons over 42 months or of those involving Boolean reached significance. Conclusions: The persistence of 14–3-3η levels ≥0.50 ng/ml appears to be associated with a lower probability of reaching remission in polyarthritis patients. 14–3-3η levels ≥0.50 ng/ml in patients in clinical remission appear to be associated with more rapid radiographic (especially erosive) progression over the following year. A larger study is required to validate these findings, especially with the most stringent criterion of Boolean remission. Disclosure of Interest: N. Carrier: None declared, M.-P. Garant: None declared, A. Marotta Employee of: Augurex Life Sciences Corp., A. De Brum Fernandes Grant/research support from: AJdBF is part of the Centre de Recherche Clinique from the CHUS, which received a team grant from the Fonds de Recherche en Santé-Québec, P. Liang: None declared, A. Masetto: None declared, Y. Gui Employee of: Augurex Life Sciences Corp., J. Savill Employee of: Augurex Life Sciences Corp., S. Michienzi Employee of: Augurex Life Sciences Corp., W. Maksymowych Consultant for: Augurex Life Sciences Corp., G. Boire Grant/research support from: GB is part of the Centre de Recherche Clinique from the CHUS, which received a team grant from the FRSQ. GB is the recipient of CIHR grant MOP-110959. Since 2007, the Sherbrooke EUPA cohort has also received financial support from the Canadian ArTritis CoHort (CATCH), a study designed and implemented by investigators and financially supported via unrestricted research grants initially by Amgen Canada Inc